2022
DOI: 10.1097/meg.0000000000002428
|View full text |Cite
|
Sign up to set email alerts
|

High plasma soluble thrombomodulin levels indicated poor prognosis of decompensated liver cirrhosis: a prospective cohort study

Abstract: Objective Hepatic sinusoidal endothelial injury is a prominent characteristic of liver cirrhosis. We determined plasma soluble thrombomodulin (sTM) levels in cirrhosis patients to evaluate the relationship between vascular injury and long-term prognosis. Methods A prospective single-center study was performed. The participants were followed up for every 6 months or until death or transplantation. A chemiluminescent enzyme immunoassay was used to establish a baseline sTM. Results Among the 219 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Some coagulation indicators were found to be correlated with plasma TM concentrations, such as PT, D dimer and INR, thus reflecting its important role in coagulation dysfunction. Since plasma TM is metabolized mainly by the liver and kidney, renal dysfunction can also result in an increase in plasma TM concentrations, 11 which may explain the positive correlation between Cr, serum urea, and plasma TM concentrations. Systemic inflammation is a major factor in determining the development, course, and prognosis of ACLF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some coagulation indicators were found to be correlated with plasma TM concentrations, such as PT, D dimer and INR, thus reflecting its important role in coagulation dysfunction. Since plasma TM is metabolized mainly by the liver and kidney, renal dysfunction can also result in an increase in plasma TM concentrations, 11 which may explain the positive correlation between Cr, serum urea, and plasma TM concentrations. Systemic inflammation is a major factor in determining the development, course, and prognosis of ACLF.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study found that high plasma soluble TM concentrations indicated poor prognosis of decompensated liver cirrhosis. 11 Analysis from a multicenter randomized controlled trial revealed that TM was associated with increased mortality rates and organ failure in children with acute respiratory failure who were ventilated mechanically. 25 One possible mechanism for the correlation between elevated plasma TM concentrations and poor clinical outcome is intravascular thrombosis, resulting in microcirculatory disturbance and multiorgan failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation